Penyamaan Batas Usia Minimum Perkawinan dalam Undang-undang Perkawinan: Analisis Maqāṣid Syarīʻah ʻAbd Allāh ibn Bayyah - Aini, Qurrotul; Ludfi, Ludfi (Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research wants to describe and analyze the provisions on the same minimum age for marriage in UU/16/2019 in terms of the maqāṣid syarīʻah ʻAbd Allāh ibn Bayyah, one of the contemporary and famous ulama, especially in Europe, with his ijtihad method which relies on reality jurisprudence. The discussion concentrates on the maṣlaḥah aspects of these provisions and exploring the concept of maqāṣid syarīʻah ʻAbd Allāh ibn Bayyah and its relevance to these provisions. This research is a type of library research using a content analysis approach. The data collection technique is in the form of documentation which consists of three steps: data inventory, data classification and data evaluation which was analyzed descriptively. The results of the research show: first, philosophically and sociologically the provisions on the same minimum age for marriage in UU/16/2019 have met the maṣlaḥah benchmarks in the aspects of ḥifẓ an-nafs and ḥifẓ an-nasl which are at the ḍarūriyah level. Second, Ibn Bayyah's concept of maqāṣid syarī'ah is a form of revitalization of maqāṣid syarī'ah side by side with uṣūl fiqh in an integrative manner through exploring law that works systemically by emphasizing the integration of three legal aspects: an-nuṣūṣ asy-syarī'ah (texts religious); al-wāqi' (social reality); and maqāṣid (spirit of law), thus placing Ibn Bayyah's concept of maqāṣid sharī'ah based on reality fiqh which combines the laws of Islamic shari'ah and the demands of the times. In Ibn Bayyah's perspective, the provisions on equal minimum marriage age limits in UU/16/2019 have fulfilled the maqāṣid syarī'ah element by avoiding mafāsid (difficulties) through an-Naẓar ila al-Ma'ālat (paying attention to future consequences) in the context of family law in the aspect of caring for the soul and offspring is at the ḍarūriyah level which stands firmly based on the principle of public benefit which covers all levels of society.